GAYA BAHASA TEKS PIDATO PRESIDEN REPUBLIK INDONESIA JOKO WIDODO - Saputra, Erlan (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Style of Text The President of the Republic of Indonesia Joko Widodo. The purpose of this study, is to describe the type of language style based on the structure of sentences and the direct meaning of meaning by using the theory of Gorys Keraf language style. This research uses a qualitative descriptive method. The data in this study are the text of the speech of the President's Elected Joko Widodo victory. Data sources in this study, namely the online news Tribunnews.com Sunday edition, July 14, 2019. The results of this study are: (1) Joko Widodo is more likely to use the climax language style. Other findings of language style, anticlimax, parallelism, antithesis, and repetition; (2) Joko Widodo also uses the style of asindeton and polindeton. The language style that is found is hyperbolic.